Comprehensive pulsed electric field (PEF) system analysis for microalgae processing. (October 2018) - Buchmann, Leandro; Bloch, Robin; Mathys, Alexander
Graphical abstract: Highlights: Ultrasonic Doppler velocity profiling for noninvasive flow field measurement. Stress-controlled rheological analysis of Arthrospira platensis suspensions. Multiphysics simulation-based system characterization and experimental validation. Comprehensive PEF system analysis facilitating reproducibility of results. Decreasing process energy for sustainable and economical biorefinery concepts. Abstract: Pulsed electric field (PEF) is an emerging nonthermal technique with promising applications in microalgae biorefinery concepts. In this work, the flow field in continuous PEF processing and its influencing factors were analyzed and energy input distributions in PEF treatment chambers were investigated. The results were obtained using an interdisciplinary approach that combined multiphysics simulations with ultrasonic Doppler velocity profiling (UVP) and rheological measurements of Arthrospira platensis suspensions as a case study for applications in the biobased industry. UVP enabled non-invasive validation of multiphysics simulations. A. platensis suspensions follow a non-Newtonian, shear-thinning behavior, and measurement data could be fitted with rheological functions, which were used as an input for fluid dynamics simulations. Within the present work, a comprehensive system characterization was achieved that will facilitate research in the field of PEF processing.